PREVALENCE OF INTERNAL AND EXTERNAL ROOT RESORPTION IN PERMANENT ANTERIOR TEETH USING DIGITAL AND DIGITALIZED PERIAPICAL RADIOGRAPHS - Travassos, Rosana Maria Coelho; Moisés, Larianne de Sousa; da Silva, Ana Roberta Negromonte; Silva, Douglas Hilderlandson das Neves; Bezerra, Amanda Nascimento Cavalcanti; Oliveira, Ana Caroline Chalegre de; Prado, Victor Felipe Farias do; Júnior, Paulo Maurício Reis de Melo (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2022)
Objetive: This study aimed to evaluate the prevalence of internal and external resorption in periapical digital radiographs in permanent anterior teeth of patients attended in a private clinic of radiology in the city of Recife, Pernambuco, Brazil, in a period of three years. Study Design: A retrospective and observation study design was realized with the aim of observing an presence of events. A total of 4630 radiographs were analyzed from the archives of the clinic. Thus, it was observed the presence of internal and external root resorption and their location in in digital and digitalized periapical radiographs.Results: It was observed more external than internal resorption (99,65%) and the teeth most affected by dental resorptions were the upper incisors (11,8%). The apical and cervical thirds were also involved with the same frequency in internal resorption while the apical third was the most involved in external resorption. Conclusion: Digital radiograph has a important and essential paper in correct diagnosis of root resorption and to conduct a correct endodontic treatment.